2022
DOI: 10.1126/sciadv.abo4610
|View full text |Cite
|
Sign up to set email alerts
|

Wide-range robust wireless power transfer using heterogeneously coupled and flippable neutrals in parity-time symmetry

Abstract: Recently, stationary wireless power transfer (WPT) has been widely adopted in commercial devices. However, the current WPT configuration is limited in its operational area and susceptible to operating condition changes, impeding its applications for dynamic environments. To overcome the limitations, we propose a WPT system with laterally aligned neutral elements in parity-time (PT) symmetry, which can widen the operational area with the number of neutrals N . Compared to the conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The operation at the low eigen frequency comes from low damping ratio, which is consistent with Ref. 43. Therefore, we have confirmed that the operation frequency is tuned as we designed.…”
Section: Robustness Of the Wirelessly Powered Motor System Against Th...supporting
confidence: 89%
“…The operation at the low eigen frequency comes from low damping ratio, which is consistent with Ref. 43. Therefore, we have confirmed that the operation frequency is tuned as we designed.…”
Section: Robustness Of the Wirelessly Powered Motor System Against Th...supporting
confidence: 89%
“…The analysis showed that the proposed system consistently and reliably provides wireless power across a wider range of both distal and lateral displacements when compared to the conventional system (Figure 32e, f). 674 In contrast, far-field technologies like Bluetooth, Wi-Fi, and 5G offer long-range, high-data rate transmission but require power at the sensor. This could be achieved by an integrated Bluetooth Low Energy (BLE) module (Figure 32g).…”
Section: Connectivity Technologiesmentioning
confidence: 99%
“…The suitability of this proposed system for biological applications and its durability were evaluated using porcine tissue in an ex vivo setting, and the results were compared to those obtained with conventional WPT systems. The analysis showed that the proposed system consistently and reliably provides wireless power across a wider range of both distal and lateral displacements when compared to the conventional system (Figure e, f) …”
Section: Ldn-based Integration and Systemsmentioning
confidence: 99%
See 2 more Smart Citations